Novel test designs for assessing the shear fracture forming limit in thin-walled tubes - Suntaxi, Carlos; López-Fernández, José Andrés; Centeno Báez, Gabriel; Vallellano Martín, Carpóforo (Elsevier, 2025)
Thin-walled tubes are used for the manufacturing of essential components in several industries. Indeed, the characterization of their formability and failure is vital for tool design, product quality and safety. In the recent years, the number of procedures and test designs for characterizing tubes in forming has experienced a significant development. This progress has been achieved in combination with the use of digital image correlation techniques and finite element analysis, making use of different plastic anisotropy criteria. Nevertheless, most of those tests are aimed at the assessment of failure in mode I of fracture mechanics, being the analysis of fracture under in-plane shear, i.e. mode II of fracture mechanics, reduced to a very limited number of research works based in the adaptation of the corresponding sheet metal forming tests inducing shear. To this regard, this work presents two new procedures based on the specific thin-walled tube geometry for characterizing formability in-plane shear and failure in mode II of fracture mechanics, addressing the absence of specific experimental methods for evaluating the shear fracture forming limit (SFFL) for tubes. The results, based on a combined numerical modelling and experimental analysis of the proposed tests, show that the SFFL can be accurately evaluated by controlling a set of geometrical parameters in the specimens designed to generate shear in tubes by applying either tensile or compressive forces. These proposed tests provide a valuable tool for characterizing the SFFL of thin-walled tubes.
Keywords: Materiales; Estructuras (Construcción); Shear fracture forming limit (SFFL); Forming limit diagram (FLD); Thin-walled tube; Shear; Fracture